A scoping review of Deaf awareness programs in Health professional education - Julia Terry (PLOS Global Public Health, 2024)
Deaf awareness aims to promote understanding about Deaf and hard of hearing people,with the goal of reducing barriers between Deaf and hearing populations; and is particularlypertinent for health professional students as they need to learn to communicate effectivelywith a range of population groups. This scoping review aims to provide an overview of literatureexamining Deaf awareness programs provided to health professional students duringtheir initial training. We searched four medical and public health databases and registersusing terms related to Deaf awareness. We used the PRISMA-ScR reporting standardschecklist for scoping reviews. We identified 10,198 citations, with 15 studies included in thefinal review. Searches were performed during August to September 2022, and April 2023.Studies were included provided they examined Deaf awareness content or programs withinhealth professional education. Data were extracted by two independent reviewers whoscreened all abstracts using Rayyan software, followed by discussion to achieve knowledgesynthesis and agreement. In all, a total of 15 articles from six countries were identifiedacross health professional student disciplines including pharmacy, nursing, audiology, interprofessionaland medical programs. The review found sparse evidence of research intoDeaf awareness programs delivered to health professional students, with delivery oftensolely to small groups of students, indicating why so few students can access informationabout how to communicate effectively with Deaf and hard of hearing patients during their initialtraining programs. This scoping reviewed showed evidence of promising benefits forhealth professional students undertaking Deaf awareness programs during their undergraduateeducation. The importance of communicating with Deaf and hard of hearing patientsand attaining Deaf cultural competencies for health professional students should be investigatedin future research.